Neurotoxic effects of MPTP on mouse cerebral cortex: Modulation of neuroinflammation as a neuroprotective strategy - Mendes, Mariana Oliveira (2019)
Parkinson's disease (PD) is a progressive neurological disorder, mainly characterized by the progressive loss of dopaminergic neurons in the Substantia nigra pars compacta (SNpc) and by the presence of intracellular inclusions, known as Lewy bodies. Despite SNpc being considered the primary affected region in PD, the neuropathological features are confined solely to the nigro-striatal axis. With disease progression other brain regions are also affected, namely the cerebral cortex, although the spreading of the neurologic damage to this region is still not completely unraveled. Tauroursodeoxycholic acid (TUDCA) is an endogenous bile acid that has been shown to have antioxidant properties and to exhibit a neuroprotective effect in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mice model of PD. Moreover, TUDCA anti-inflammatory properties have been reported in glial cells, making it a prominent therapeutic agent in PD. Here, we used C57BL/6 mice injected with MPTP in a sub-acute paradigm aiming to investigate if the neurotoxic effects of MPTP could be extended to the cerebral cortex. In parallel, we evaluated the anti-oxidant, neuroprotective and anti-inflammatory effects of TUDCA. The anti-inflammatory mechanisms elicited by TUDCA were further dissected in microglia cells. Our results show that MPTP leads to a decrease of ATP and activated AMP-activated protein kinase levels in mice cortex, and to a transient increase in the expression of antioxidant downstream targets of nuclear factor erythroid 2 related factor 2 (Nrf-2), and parkin. Notably, MPTP increases pro-inflammatory markers, while down-regulating the expression of the anti-inflammatory protein Annexin-A1 (ANXA1). Importantly, we show that TUDCA treatment prevents the deleterious effects of MPTP, sustains increased levels of antioxidant enzymes and parkin, and most of all negatively modulates neuroinflammation and up-regulates ANXA1 expression. Additionally, results from cellular models using microglia corroborate TUDCA modulation of ANXA1 synthesis, linking inhibition of neuroinflammation and neuroprotection by TUDCA.